Perilaku pencarian informasi mahasiswa magister dan doktor fully online dalam menyelesaikan studi di Universitas Terbuka - Riady, Yasir; Riady, Hamdi; Arisanty, Melissa; Wahyu, Milde (UPT Perpustakaan Universitas Islam Negeri Walisongo, 2023)
Background. As one of the open and distance universities, Universitas Terbuka provides access to higher education for all Indonesian people without exception, this is also stated in the vision and mission of the Open University to be able to provide the widest possible service, which comes all students with normal or disabilities. This study aims to find and see information seeking behavior by students with special needs at the Open UniversityMethodology. The research method uses observation and interviews for analyses and looking at facts in the field to get detailed information in this research.Results and discussion. This study wants to observe the need and the behavior of information of students with special needs at Universitas Terbuka, it can be seen what model is used by students with special needs and can be used as one of the inputs and suggestions that need to be acknowledged by the Universitas Terbuka. Based on the analytical data that has been carried out as well as interviews with informant sources the information needed by students is closely related to the topic of their study needs or tasks, so students need a variety of references for their knowledge and needs in completing their studies at the Universitas Terbuka.Conclusions. Most information popular and often used by students are printed books and internet sources because they contain up-to-date, relevant information and easy use and provide detailed and basic information for both administrative and academic with special needs.